A novel method: ionic liquid-based ultrasound-assisted extraction of polyphenols from Chinese purple yam. Issue 7 (3rd April 2018) - Zhang, Junhong; Zong, Aizhen; Xu, Tongcheng; Zhan, Ping; Liu, Lina; Qiu, Bin; Liu, Wei; Jia, Min; Du, Fangling; Tian, Honglei
Abstract: Chinese purple yam is famous for therapeutic and nutritional values in lowering blood glucose, blood pressure and even preventing and treating cardiovascular diseases. However, traditional extraction techniques for the functional polyphenolic compounds mostly utilise unfriendly organic solvent and easily cause degradation of polyphenols. In this study, a novel ionic liquid-based ultrasound-assisted extraction (IL-UAE) technique was utilised to obtain polyphenols. The optimal extraction condition included: solid–liquid ratio (0.05 g/mL), ionic liquid concentration (1.05 M), extraction temperature (67°C) and ultrasonic time (37 min). The maximum free radical scavenging activity (86.21%) and total antioxidant activity (2.21 mM) were achieved and matched well with the predicted values, superior to that of the extract from regular ethanol-based UAE. IL-UAE could be a rapid and green technique for efficient extraction of polyphenols from purple yam with low solvent consumption and few structural deterioration, exhibiting application potential in food and pharmaceutical industries. Abstract :